PENGARUH CONTENT MARKETING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN JAM TANGAN MEREK ALEXANDRE CHRISTIE (Studi Kasus Pada Toko Tickclock Kota Bengkulu) - Alpino, Nopiyen; Arini, Eti (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research aims to determine the influence of Content Marketing and Product Quality on Purchase Decisions for Alexandre Chritie Brand Watches (case study at the Tickclock Store in Bengkulu City), both partially and simultaneously. There are several factors that will be discussed in this research, including Content Marketing and Product Quality. The object of this research is consumers at the Tickclock watch shop, precisely located on Jl. Putri Gading Cempaka No. 6, Bawah, Ratu Samban District, Bengkulu City. The sampling method uses a non- probability technique, namely accidental sampling. The number of respondents in this research was 140 respondents. The data collection method used a questionnaire. The data analysis technique in this research uses instrument testing, classical assumption testing, respondent response analysis, multiple linear regression analysis, hypothesis testing and coefficient of determination analysis. The results of this research show that Content Marketing has a positive and significant effect on purchasing decisions, then Product Quality has a positive and significant effect on purchasing decisions. So, from the results of the research that has been carried out it can be concluded that Content Marketing and Product Quality have a partial and simultaneous influence on the decision to purchase Alexandre Chritie brand watches at the Tickclock Store in Bengkulu City Keywords: Content Marketing, Product Quality and Purchasing Decisions